THE EXAMINER'S POINT OF VIEW. - Webster, Norman E. (The Accounting Review, 1937)
Abstract Accountant's work in finding of facts may be a factor in court actions, which are not primarily for money though they relate to it. The entire population of a state and of other states have an interest in the qualification of those to whom the state gives these certificates. Next perhaps is the interest of those in practice holding the certificate individually and through their professional societies are striving to maintain the position, which the profession has attained and to advance it still further in the esteem of public. Then there are educators, those organized in the schools of business, both resident and correspondence, those who give private instruction and conduct coaching courses and those often overlooked in this connection, who as the employers of beginners in accountancy, direct their reading and of even more importance, give oral instruction in principles as they explain the relation of the principles to the matter then in hand. Legislature to cheek the qualification of bar candidates, investigate charges of unethical and illegal practices.